Case Study As A Tool For Stimulating Professional Self-Development Of A Teacher-Educator - Natalia Chirkova; Natalia Chirkova; Oksana Pavlova; Irina Burlakova; Elizaveta Burlakova (ARPHA Proceedings, 2022)
A survey of students and in-service teachers showed that the awareness of the need for professional self-development occurs already in the process of training at a pedagogical university. The question of finding tools to stimulate this process among in-service teachers remains open.The case study is based on a specially modelled real professional-practical situation to analyze and identify problem areas, search for alternative ways to resolve it, and select the most optimal and acceptable one for a particular respondent. This technology provides both the interiorization of knowledge already known to science and the acquisition of objectively new knowledge located in the subject area of the case being solved. Thus, the potential of a case study allows us to consider it as a real pedagogical tool for stimulating the professional self-development of a teacher. The purpose of the study is to identify this potential and describe a possible approach to its implementation to stimulate the professional self-development of a teacher-educator. The following methods were chosen: a review of scientific and methodological literature on the research problem; systematization of research ideas; questioning; generalization of empirical experience. A questionnaire survey of future and practising teachers showed their readiness to master this tool of professional self-development in the absence of experience in its direct use to solve the problem. The developed approach assumes a phased deployment of an acquaintance of students and practising teachers with a case study as a tool for professional self-development and presupposes involvement in the design of cases.